RESTORATIVE JUSTICE SEBAGAI PEMBAHARUAN SISTEM PERADILAN PIDANA BERDASARKAN UU NO.11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Lidya Rahmadani Hasibuan; Muhammad Hamdan; Marlina Marlina; Utary Maharani Barus (Universitas Sumatera Utara, 2015)
ABSTRACT Formation basis of Restorative Justice’s concept in Indonesia originated from a variety of tribal customary law. As customary of Minangkabau, Mandailing, Toraja, Bali and others have done this concept known as the consensus agreement. Restorative Justice’s concept is also known in 1970 in Canada. Restorative Justice’s concept implemented in Article 7 of Law Number 11 of 2012 by using the Diversion way. Potencies are available when applying Restorative Justice’s concept is the Institutional and Professionals of Law Enforcement Officer substantively has been guaranteed in the Law Number 11 of 2012 added many people who support the implementation of Restorative Justice’s concept in Juvenile Justice System in the foreseeable future. Constraints that will be faced by law enforcement officer is the human resources who have not been able to fulfill what is mandated by law Number 11 of 2012, namely the existence of a Judge, Prosecutor and police for child which is a must in every agencies. Inadequate infrastructure in every law enforcement officer agencies is also an obstacle for the future implementation of the Restorative Justice’s concept, and the legal culture of society that many complained by law enforcement officer that can be complicate the implementation of Restorative Justice’s concept in the Juvenile Justice System. Keywords:RestorativeJustice,Juvenile Justice System, Law Enforcement Officer